Write out the solution to the equation : x + y - z = 0, 2x + 4y - z = 0 and 3x + 2y + 2z = 0
in Algebra 1 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

first equation:

x + y - z = 0

x + y = z

in the other 2 equations, replace z with x + y:

2x + 4y -(x+y) = 0

3x + 2y +2(x+y) = 0

simplify:

2x + 4y -x -y = 0

3x + 2y +2x +2y = 0

simplify more:

x + 3y = 0

5x + 4y = 0

in the top equation, move the 3y to the other side:

x = -3y

in the bottom equation, replace x with -3y:

5(-3y) + 4y = 0

-15y +4y = 0

-11y = 0

y = 0

but x = -3y, so:

x = -3(0)

x = 0

but x + y - z = 0, so:

0 + 0 - z = 0

z = 0

Answer:  x = 0, y = 0, z = 0
by Top Rated User (103k points)

Related questions

Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
86,974 questions
95,835 answers
2,361 comments
24,325 users